Economic consequences of private equity investments on the German stock market - Ann-Kristin Achleitner; Christian Andres; André Betzer; Charlie Weir (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
This paper investigates the wealth effects of private equity (PE) investor purchases of shares in German quoted companies. It is the first study to analyze these effects for the German market which is particularly interesting due to its distinct characteristics with regard to the ownership structure of publicly listed companies and the protection of minority shareholders. We find that PE investors generate positive wealth effects for target shareholders of 5.90% around the event day (t = -1 to t = 0). In addition, we find that the wealth effects of PE investor involvement in Germany are positively related to the target's tax liabilities and degree of undervaluation and negatively related to the target's leverage and the shareholding of the second largest ownership block. The latter effect can be interpreted as a supplementary monitoring effect of the management or a monitoring effect of the largest shareholder through which private benefits of control are reduced.
Keywords: G14; G32; G34; 330; Private Equity; Corporate Governance; Agency Theory; Event Study; Private Equity; Corporate Governance; Prinzipal-Agent-Theorie; Aktiengesellschaft; Deutschland